2019
DOI: 10.3390/pharmaceutics11050239
|View full text |Cite
|
Sign up to set email alerts
|

Vibrating Mesh Nebulisation of Pro-Antimicrobial Peptides for Use in Cystic Fibrosis

Abstract: Background: There has been considerable interest in the use of antimicrobial peptides (AMPs) as antimicrobial therapeutics in many conditions including cystic fibrosis (CF). The aim of this study is to determine if the prodrugs of AMPs (pro-AMPs) can be delivered to the lung by a vibrating mesh nebuliser (VMN) and whether the pro-AMP modification has any effect on delivery. Methods: Physical characteristics of the peptides (AMP and pro-AMP) and antimicrobial activity were compared before and after nebulisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Some studies have also demonstrated that it is possible to generate a respirable aerosol of antimicrobial peptides (AMPs) or prodrug AMPs. The AMP prodrug and its active peptide component were both unchanged after VMN and maintained their levels of antimicrobial activity against the most common CF pathogen, P. aeruginosa [56].…”
Section: Antibioticsmentioning
confidence: 92%
See 2 more Smart Citations
“…Some studies have also demonstrated that it is possible to generate a respirable aerosol of antimicrobial peptides (AMPs) or prodrug AMPs. The AMP prodrug and its active peptide component were both unchanged after VMN and maintained their levels of antimicrobial activity against the most common CF pathogen, P. aeruginosa [56].…”
Section: Antibioticsmentioning
confidence: 92%
“…Aerogen Ltd. VMN technologies are the dominant device platform for mechanical ventilation trials [1]. This platform has been shown to retain the bioactivity of antibiotics [51], gene vectors [54], inhaled vaccines [55], or proteins [56,57]. The clinical effectiveness of VMN has been demonstrated in outcomes such as shorter ICU stays compared to MDI and JN in mechanically ventilated asthmatic patients [58].…”
Section: Advantages Of Vibrating Mesh Nebulizers In Mechanical Ventilmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, mesh nebulisers appear to maintain protein integrity to a greater extent than other nebulisers [ 32 ]. Safe aerosolisation with mesh nebulisers has already been demonstrated in several studies of labile drugs including proteins and mAbs [ 33 38 ]. The detailed designs and comparisons of various types of nebulizers have been reviewed previously and we will not elaborate further here [ 25 , 30 32 , 39 ].…”
Section: Challenges and Considerations In The Development Of Protein mentioning
confidence: 99%
“…AMPs do not only have direct antimicrobial activity, but also modulate the immune system and wound repair, making them of interest in CF therapy. Forde and colleagues studied whether prodrugs of AMPs (pro-AMPs) can be delivered by VMN and whether modifications of pro-AMP had an effect on the delivery [ 13 ]. Nebulisation did not alter AMPs’ physical characteristics and antimicrobial activity.…”
Section: Inhaled Antibioticsmentioning
confidence: 99%